Investigations on amidoxime grafted sepiolite based chitosan organic–inorganic nanohybrid composite beads towards wastewater detoxification - Mohib Ullah Khan (Elsevier, 2022)
This work explores the fabrication of organic–inorganic nanohybrid based biopolymer composite systems for the cleaning of different contaminants from wastewater. This system involves the simultaneous radiation grafting techniques for sepiolite (SP) modification and the simple mixing of modified-SP with biopolymer matrix, chitosan (CS). The SP beads were chemically modified with amidoxime prior to its use in composite systems. The synthesized composite beads were characterized using scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), nitrogen physical adsorption (BET) investigations, Fourier transform infrared (FT-IR), atomic absorption and UV–visible spectroscopy. Hydrolytic stability of beads was also investigated in aqueous media, beads showed excellent stability in aqueous medium and in acidic environment. Here, the sorption profile of copper over amidoxime grafted SP-nanohybrid (MSP) incorporating CS-beads is reported. Furthermore, the key adsorptive variables, i.e. contact time, adsorbent dose, and concentration of adsorbate are discussed. Different isothermal (Langmuir and Freundlich) and kinetics model were also elaborated. Langmuir isotherm and pseudo-second-order models are proved to be the best fit models for Cu (II) removal in aqueous system. To explore the efficacy of the material towards organic pollutants, methylene blue (MB) was selected as model compound and adsorbed on nanohybrid beads. The results revealed that organic–inorganic nanohybrid incorporating CS beads are quite effective for contaminated water remediation, owing to their better adsorptive performance, high stability and easy application.